Stereotip pada Masyarakat Padangbolak dan Mandailing di Desa Pargarutan Julu Kecamatan Angkola Timur Kabupaten Tapanuli Selatan - Sri Wahyuni Harahap; Payerli Pasaribu (Universitas Negeri Medan, 2019)
The purpose of this study was to find out the perceptions, impacts and barriers of communication on the social relations of Padangbolak people and Mandailing people with other tribes with the nickname of the gutgut ni halak, Padang, and the Mandailing halak for the Padangbolak people and the Mandailing people towards the nickname of the Halak Mandailing colony. To achieve this goal, this study uses a descriptive approach research method with research subjects namely Padangbolak and Mandailing people who settled in Pargarutan Julu Village, Angkola Timur sub-district, South Tapanuli district, by conducting direct observations in the field and conducting interviews determined through Purposive sampling that is to determine the informant intentionally by using the criteria set by the researcher. The results of the study show that the stereotypes are formed by social categories which are individual efforts to understand their social environment. In other words, when individuals face so many people around them, individuals will look for similarities between certain people and group them into one category. But in turn this social category actually affects the perspective of someone who has been included in the group.